Enhancement of Universiti Teknologi Malaysia image map using Garmin handheld receiver - Othman, Nur Liyana (2009)
Maps form an integral part of planning. There are different techniques by which, maps are prepared, depending upon the purpose and accuracy required. The different techniques, range from simple chain and tape measurements to optical methods and further to satellite based technologies. Access to GPS technology has led to advances in techniques for many applications, dramatically upgrading the process of collecting new data and providing a cost-effective means for refreshing the old. A part of the GPS technology is the invention of receivers that are specially used for data collection. The objective of this study is to implement the capabilities of a handheld GPS unit to produce an enhanced image map for the UTM campus. In this study, road features were collected using Garmin GPSMAP 76CSx handheld unit. The road features were then combined together with a base map that was created using Google Maps. Highlighting the places of interest in the UTM image was applied to give the image map an additional feature. The product of this study is an updated version of the UTM campus map that contains enhanced building details from Google Maps and also the latest road tracks that were not displayed in the previous maps. The GPS measurements were proven to be capable in producing small and large scale maps. The use of GPS technologies particularly handheld equipments are effective especially in producing updated maps in the short time.